2010
DOI: 10.1123/jsep.32.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Be Active and Become Happy: An Ecological Momentary Assessment of Physical Activity and Mood

Abstract: The positive effects of physical activity on mood are well documented in crosssectional studies. To date there have been only a few studies analyzing withinsubject covariance between physical activity and mood in everyday life. This study aims to close this gap using an ambulatory assessment of mood and physical activity. Thirteen participants completed a standardized diary over a 10-week period, resulting in 1,860 measurement points. Valence, energetic arousal, and calmness are the three subscales of mood tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 19 publications
12
119
5
3
Order By: Relevance
“…Regarding the effect of aPA on affective states, we show that the more our subjects were physically active, the more they felt well (valence), awake (energetic arousal), but agitated (calmness [-]). Earlier studies have already demonstrated that even unstructured lifestyle physical activities of low-to-moderate intensities can positively affect a person's affective state (Kanning & Schlicht, 2010). Similarly to our study, these authors have assessed data during real-life situations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Regarding the effect of aPA on affective states, we show that the more our subjects were physically active, the more they felt well (valence), awake (energetic arousal), but agitated (calmness [-]). Earlier studies have already demonstrated that even unstructured lifestyle physical activities of low-to-moderate intensities can positively affect a person's affective state (Kanning & Schlicht, 2010). Similarly to our study, these authors have assessed data during real-life situations.…”
Section: Discussionmentioning
confidence: 87%
“…This gave us the opportunity to question participants even in the course of ongoing physical activities. Maybe the relaxing effects (calmness [+]) of aPA, as reported in the study of Kanning and Schlicht (2010), appear only after a time delay when the direct experience of having been physically active has been reevaluated. Future studies should assess the association of aPA and sense of calm in more detail by using different time lags.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, happiness and satisfaction were among the variables that were most highly linked with regular physical activity. The possible reason is that physical activity has positive impacts on individual mood and emotional state [25]. For instance, a study has shown that physically active people show positive emotions, including excitement, enthusiasm, and happiness [26]; 10-15 minutes of vigorous walking can help enhance individual mood states [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the change of this kind is consequences of everyday decisions that assemble over time. Previous research has identified social influences and supports play a critical role in encouraging and retaining the change [1,2]. Can the pervasiveness and technological capabilities of smartphones be designed to enable the change and if so, how to leverage the materialities of smartphones to embody the social effect on motivating people for cycle commuting?…”
Section: Introductionmentioning
confidence: 99%